Sosialisasi Anti-Bullying dan Kekerasan Seksual: Upaya Mewujudkan Lingkungan Belajar yang Aman dan Nyaman di SDN 01 Tosari - Mohammad Nayaka Rama Yoga; Mutiara Mustika Suryandani; Mohammad Rangga Patmanegara; Fara Delya Zevira; Tia Nur Azizah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The socialization of anti-bullying and sexual violence in elementary schools is a crucial step in creating a safe and comfortable learning environment for students. This article discusses effective socialization strategies, the roles of teachers and parents, and the impact of these activities on student behavior. A case study was conducted in several elementary schools in [City Name], showing a decrease in bullying and sexual violence incidents following the socialization efforts. Recommendations for broader implementation are also provided.